(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Researches in the area of facial expressions have been made since at least the last two centuries, and focus on two main perspectives: the evolutionist and culturalist. Paul Ekman was the responsible for the articulation of these, bringing several contributions to the field of psychology, specifically to the clinical context. The objective of this study was to identify possible contributions of the work of facial expressions of Paul Ekman and his collaborators for the behavior-analytic clinic. Differently from what can be found in the traditional literature, our study made possible the verification of facial expressions as verbal and nonverbal behavior. This reinforces the importance of specific training of psychotherapist to expand the repertoire to attend in clinical work, paying attention to the relation between psychopathology and facial expressions.